2019
DOI: 10.1016/j.jaci.2019.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Frontiers in alopecia areata pathobiology research

Abstract: This current review explores selected and as yet insufficiently investigated frontiers in current alopecia areata (AA) pathobiology research, with an emphasis on potential ''new'' players in AA pathobiology that deserve more systematic exploration and therapeutic targeting. Indeed, new evidence suggests that CD8 1 T cells, which have long been thought to be the central players in AA pathobiology, are not the only drivers of disease. Instead, subsets of natural killer (NK) and so-called ''unconventional'' T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 148 publications
(256 reference statements)
2
59
0
4
Order By: Relevance
“…This supports the concept that pathological mast cell‐T cell interactions may contribute to the pathogenesis of human AA, perhaps particularly so in atopic individuals 6,44,179 . Recent experiments have demonstrated that the AA phenotype can also be triggered by non–antigen‐specific innate lymphocytes such as type 1 innate lymphoid cells 44,284 . Therefore, besides mast cells, several innate and adaptive immune cell lineages may be functionally important in AA pathogenesis.…”
Section: Hair Follicle Immune Privilege Collapse As a Prerequisite Fosupporting
confidence: 74%
See 4 more Smart Citations
“…This supports the concept that pathological mast cell‐T cell interactions may contribute to the pathogenesis of human AA, perhaps particularly so in atopic individuals 6,44,179 . Recent experiments have demonstrated that the AA phenotype can also be triggered by non–antigen‐specific innate lymphocytes such as type 1 innate lymphoid cells 44,284 . Therefore, besides mast cells, several innate and adaptive immune cell lineages may be functionally important in AA pathogenesis.…”
Section: Hair Follicle Immune Privilege Collapse As a Prerequisite Fosupporting
confidence: 74%
“…Mast cells strikingly switch from an immunoinhibitory phenotype and infrequent interactions with CD8 + T cells to a profoundly pro‐inflammatory phenotype and greatly enhanced interactions with CD8 + lymphocytes, and—highly unusual for mast cells—even proliferate around lesional HFs in situ 179 . This supports the concept that pathological mast cell‐T cell interactions may contribute to the pathogenesis of human AA, perhaps particularly so in atopic individuals 6,44,179 . Recent experiments have demonstrated that the AA phenotype can also be triggered by non–antigen‐specific innate lymphocytes such as type 1 innate lymphoid cells 44,284 .…”
Section: Hair Follicle Immune Privilege Collapse As a Prerequisite Fomentioning
confidence: 54%
See 3 more Smart Citations